HADIS-HADIS KUCING DALAM PANDANGAN MULA ALI AL-QARI: Kajian Kitab Risalah Al-Birrah Fi Hubb Al-Hirrah - Musaffa, Arini Silma; Hidayati, Hidayati (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
This study aims to find out the views of Mula Ali Al-Qari on the traditions about cats that are popular in the community. This research uses library research which in its development uses a textual-analytical approach. The primary source of this research is a short treatise by Mula Ali Al-Qari entitled